2019
DOI: 10.3390/jcm8111814
|View full text |Cite
|
Sign up to set email alerts
|

The SGLT2 Inhibitor Empagliflozin Ameliorates the Inflammatory Profile in Type 2 Diabetic Patients and Promotes an Antioxidant Response in Leukocytes

Abstract: Sodium–glucose co-transporter 2 inhibitors (iSGLT2) have been linked to a considerable reduction in cardiovascular risk in patients with type 2 diabetes (T2D), but the precise molecular mechanisms are still elusive. We aimed to evaluate the effects of the iSGLT2 empagliflozin on systemic inflammation and its potential antioxidant properties. This is an observational, prospective follow-up study of a cohort of fifteen patients with T2D who received 10 mg/day of empagliflozin according to standard clinical care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 47 publications
8
81
1
3
Order By: Relevance
“…In this sense, the present results show a reduction in the expression of the adhesion molecule ICAM-1 and the in ammatory marker hs-CRP after 24-weeks of empagli ozin treatment. These results are in accordance with those previously reported by our group showing that empagli ozin treatment reduced levels of the in ammatory enzyme myeloperoxidase -actively involved in the development of microvascular alterations [26] -and increased release of the anti-in ammatory interleukin-10 (IL-10) [15]. Considered as a whole, these data suggest that empagli ozin ameliorates the in ammatory state and reduces the risk of CVDs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this sense, the present results show a reduction in the expression of the adhesion molecule ICAM-1 and the in ammatory marker hs-CRP after 24-weeks of empagli ozin treatment. These results are in accordance with those previously reported by our group showing that empagli ozin treatment reduced levels of the in ammatory enzyme myeloperoxidase -actively involved in the development of microvascular alterations [26] -and increased release of the anti-in ammatory interleukin-10 (IL-10) [15]. Considered as a whole, these data suggest that empagli ozin ameliorates the in ammatory state and reduces the risk of CVDs.…”
Section: Discussionsupporting
confidence: 92%
“…Considered as a whole, these data suggest that empagli ozin ameliorates the in ammatory state and reduces the risk of CVDs. In support of this, empagli ozin has been shown to reverse obesity and insulin resistance through fat browning and alternative macrophage activation in mice fed a high-fat diet [27], and to reduce in ammation and boost the antioxidant response in leukocytes from type 2 diabetic patients [15].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In short, major pathophysiologic mechanisms underlying increased arterial stiffness in diabetes mellitus include the formation of advanced glycation end products (AGEs) on the arterial wall, inducing cross‐linking of collagen molecules and subsequent loss of collagen elasticity, increased activity of renin‐angiotensin‐aldosterone system (RAAS), chronic inflammation, enhanced oxidative stress, and endothelial dysfunction (Figure ) . It has been therefore shown (mainly in experimental models) that SGLT‐2 inhibition decreases the expression of AGEs and their receptor (RAGE), while it also suppresses oxidative stress and inflammatory response . It has been also demonstrated that SGLT‐2 inhibition might provide a significant, beneficial effect on endothelial dysfunction in T2DM, although results are contradictory in shorter duration studies .…”
Section: Sglt‐2 Inhibitors and Arterial Stiffness: A New Place Under mentioning
confidence: 99%